2017
DOI: 10.21873/anticanres.11882
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Carcinogenesis: Role of Oxidative Stress and Antioxidants

Abstract: One of the contributory causes of colon cancer is the negative effect of reactive oxygen species on DNA repair mechanisms. Currently, there is a growing support for the concept that oxidative stress may be an important etiological factor for carcinogenesis. The purpose of this review is to elucidate the role of oxidative stress in promoting colorectal carcinogenesis and to highlight the potential protective role of antioxidants. Several studies have documented the importance of antioxidants in countering oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 35 publications
3
45
0
Order By: Relevance
“…Over the past decade a slight decline has been observed in colorectal cancer (CRC), however; it still remains the third most common cancer among cancer patients worldwide. It has been observed that CRC is associated with old age, lifestyle factors and in some cases due to underlying genetic disorders 1 . The well-known risk factors include obesity, diet, lack of physical activity and smoking 1 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Over the past decade a slight decline has been observed in colorectal cancer (CRC), however; it still remains the third most common cancer among cancer patients worldwide. It has been observed that CRC is associated with old age, lifestyle factors and in some cases due to underlying genetic disorders 1 . The well-known risk factors include obesity, diet, lack of physical activity and smoking 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that CRC is associated with old age, lifestyle factors and in some cases due to underlying genetic disorders 1 . The well-known risk factors include obesity, diet, lack of physical activity and smoking 1 . Moreover; there are several dietary factors that have been identified to increase the risk of CRC such as; red and processed meat, and alcohol.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a general agreement that oxidative stress is closely associated with various complex physiological and pathological mechanisms [ 3 , 4 ]. In addition, there is growing support for the concept that oxidative stress plays important roles in carcinogenesis, malignant behavior, and prognosis, in various types of cancer [ 4 , 5 ]. Thus, understanding the pathological roles and regulatory mechanisms of oxidative stress in malignant cells and tissues is essential to discuss the observations and treatment strategies in patients with malignancies.…”
Section: Introductionmentioning
confidence: 99%